An extended semantic analyzer for ADA'95 - Karahan, Mehmet Özgür. (Thesis (M.S.) - Bogazici University. Institue for Graduate Studies in Science and Engineering, 2001., 2001)
An extended semantic rule is a rule which we expect a program in a particular language to obey in addition to the standard semantic rules enforced by the compiler for the language. Such extended semantic rules may be necessary to ensure that software has certain software quality attributes. In this work, an Extended Semantic Rule Set (ESRS) that contains certain semantic restrictions for Ada'95 programs is defined and the effectiveness of that rule set to increase software quality attributes of Ada codes is examined. The work done in this thesis also describes the design and implementation of a software tool, a SemantiC Analyzer (SCA) that checks the compliance of a given Ada code to the Semantic Rule Set. The effectiveness of the Semantic Analyzer is discussed on sample input and its output is analyzed for a large set of previously compiled Ada code.
Keywords: Semantics.